Animation of virtual medical system under the background of virtual reality technology. (4th April 2021) - Li, Liang; Li, Tingting
Abstract: Virtual reality technology is a technology that uses a variety of scientific technologies such as computer systems, image displays, and sensors to perform human–computer interaction. Since the advent of virtual reality technology, the virtual reality + medical model has been highly expected. At present, three‐dimensional (3D) animation technology can be used in combination with virtual reality technology in medical systems. 3D animation technology can transform the transformed human medical image into a 3D character model, and animate the corresponding bones, and observe the model on the screen and operate the model like real surgery, completing virtual medical content learning, virtual medical skill training, virtual surgery preview. Applying 3D animation technology to virtual reality surgery training can effectively bypass the limitations of traditional surgery training modes, form multiple interactive real‐time effects, and bring a rich perceptual experience to the audience. Based on the above background, the research content of this article is the study of virtual medical system animation under the background of virtual reality technology. This paper analyzes the feasibility of virtual reality technology and 3D animation modeling, and designs a virtual medical system based on this. Finally, through experimental simulations, the results show that the gap h is getting larger and larger after the first approximation, and the gap between the Euler explicit method and the true value is larger, while the implicit method is more stable, and the gap does not increases too quickly with the increase of h . Hence choosing the implicit method to calculate Δ t to obtain a larger value will not affect the stability of the solution.